Analysis of Legal Protection Regarding the Fulfillment of Copyright Owners' Royalty Rights - Amelia Anggriany Siswoyo; Dwi Sartika Paramyta; M. Rohmidhi Srikusuma; G.P. Raiwella; Yuli Grace (CV Edujavare Publishing, 2026)
Legal protection for the fulfillment of royalty rights is an important part in guaranteeing the economic rights of creators and/or copyright holders for the commercial use of works. Although Indonesia has Law Number 28 of 2014 concerning Copyright, Government Regulation Number 56 of 2021 concerning Management of Song and/or Music Copyright Royalties, and Regulation of the Minister of Law Number 27 of 2025, the implementation of the fulfillment of royalty rights still faces various obstacles, such as the less than optimal transparency of royalty management, weak coordination between the Collective Management Institution (LMK) and the National Collective Management Institution (LMKN), inaccurate data collection systems for the use of works, and low compliance of commercial users in fulfilling royalty payment obligations. This study aims to analyze the forms of legal protection for the fulfillment of royalty rights, the mechanism for withdrawal, collection, and distribution of royalties, as well as obstacles and efforts to optimize legal protection so that the fulfillment of royalty rights can be implemented effectively. The study uses a normative legal research method with a statutory and conceptual approach, through a literature study of primary, secondary, and tertiary legal materials analyzed descriptively and qualitatively. The research results indicate that normatively, regulations regarding royalty protection have provided legal certainty through preventive and repressive measures. However, the effectiveness of their implementation is still influenced by the quality of institutional governance, transparency of royalty distribution, integration of song usage data systems, and the level of public legal awareness. Therefore, strengthening inter-institutional coordination, digitizing the royalty management system, increasing transparency and accountability, and ongoing outreach are needed to achieve effective, transparent, and equitable legal protection for creators and copyright holders.